INTRAOPERATIVE ADMINISTRATION OF DEXMEDETOMIDINE DURING CARDIAC SURGERY IN CHILDREN WITH CONGENITAL HEART DEFECTS (CHD) (Herald of the National Children's Medical Center, 2025)
Congenital heart defects (CHD) are the most common congenital anomalies in children and remain a leading cause of childhood mortality. Modern diagnostic methods and surgical correction have significantly improved the survival rates of children with CHD. In this regard, the optimization of anesthetic management during open-heart surgery in young children is of particular importance. One of the promising components of anesthesia is dexmedetomidine—a selective α2-agonist with sedative, analgesic, and sympatholytic effects.
Keywords: congenital heart defects; children; cardiac surgery; dexmedetomidine; general anesthesia; cardiopulmonary bypass